Brexpiprazole for the treatment of schizophrenia. (22nd January 2017) - Hsu, Wen-Yu; Lane, Hsien-Yuan; Lin, Chieh-Hsin
ABSTRACT: Introduction : Limited efficacy on negative and cognitive symptoms and adverse effects of current antipsychotics raise the need of developing new antipsychotics. Brexpiprazole, a new antipsychotic drug approved by the U.S. Food and Drug Administration in July 2015 for the treatment of schizophrenia, is a novel serotonin-dopamine receptor modulator with partial agonist activity at serotonin 1A (5-HT1A ) and D2/3 receptors. Areas covered : We reviewed brexpiprazole related in vitro and in vivo studies, including phase II and phase III clinical trials in this article. Brexpiprazole showed significant improvement of psychotic symptoms for patients with schizophrenia in clinical trials. Most of the clinical trials demonstrated the antipsychotic effect of brexpiprazole using Positive and Negative Syndrome Scale (PANSS) in acute schizophrenia patients, and found that higher doses (2–4 mg daily) of brexpiprazole had better outcomes. In short-term trials, brexpiprazole did not show benefit for cognitive function in 6 weeks. Insomnia, akathisia, headache, and agitation were the most frequently recorded adverse events. Expert commentary : Brexpiprazole showed better efficacy than placebo in acute phase of schizophrenia. Long-term studies are needed to investigate the efficacy of brexpiprazole for cognitive function as well as the strength and weakness of brexpiprazole among current antipsychotic drugs.